Environmental change and human security recognizing and acting on hazard impacts - NATO Advanced Research Workshop on Environmental Change and Human Security : Recognizing and Acting on Hazard Impacts (NATO science for peace and security series. Series C, Environmental security, 2008)
Environmental and Human Security: Then and Now 1 2 ALAN D. HECHT AND P. H. LIOTTA * 1 U. S. Environmental Protection Agency Office of Research and Development 2 Pell Center for International Relations and Public Policy Salve Regina University 1. Nontraditional Threats to Security The events of September 11, 2001 have sharpened the debate over the meaning of being secure. Before 9/11 there were warnings in all parts of the world that social and environmental changes were occurring. While there was prosperity in North America and Western Europe, there was also increasing recognition that local and global effects of ecosystem degradation posed a serious threat. Trekking from Cairo to Cape Town thirty years after living in Africa as a young teacher, for example, travel writer Paul Theroux concluded that development in sub-Saharan Africa had failed to improve the quality of life for 300 million people: “Africa is materially more decrepit than it was when I first knew it—hungrier, poorer, less educated, more pessimistic, more corrupt, and you can’t tell the politicians from the witch-doctors” (2002). While scholars and historians will debate the causes of 9/11 for some time, one message is clear: An often dizzying array of nontraditional threats and complex vulnerabilities define security today. We must understand them, and deal with them, or suffer the consequences. Environmental security has always required att- tion to nontraditional threats linked closely with social and economic well-being. Approaches to environmental and human security -- Zombie concepts and boomerang effects -- Measuring human security -- Environmental challenges: examples from North Africa, the BAlkans, and the Middle East -- Drylands in crisis -- Desertification in Jordan -- Global environmental change and the international efforts concerning environmental conservation -- Management of environmental challenges and sustainability of Bulgarian agriculture -- Regional assessment of landscape and land use change in the Mediterranean region -- Human challenges: case studies -- Human security for an urban century -- Urbanization and environmental security -- Approaching environmental security -- The human security dilemma -- Securing humans and/or environment in the post-conflict Balkans -- Environmental justice and health disparities in Appalachia, Ohio -- Acting on hazard impacts: examples from sub-Saharan Africa, Eastern Europe, and Central Asia -- Poverty-environment linkages and their implications for security -- Human and environmental security in the Sahel -- Environment and security in eastern Europe -- Environmental issues of the Kyrgyz Republic and Central Asia -- Environmental change in the Aral Sea Region -- Environmental change of the Semipalatinsk test site by nuclear fallout contamination -- Environmental change and human impact linkages -- Summary, conclusions, and recommendations for policy and research.